ANALISIS OUTPUT DAN OUTCOME BIDANG PENDIDIKAN DALAM ERA OTONOMI DAERAH DI JAWA TENGAH - Anggraini, Hanjar Giri (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
This study is aimed to analyze the educational output and outcome in the era of autonomy policy. By using path analysis, this study tested exogenous variables on endogenous variables directly or indirectly. The educational output in this study is the graduation rate of junior secondary school/madrasah tsanawiyah (JSS/MTs), while the educational outcome is the transition rate to general senior secondary school/vocational senior secondary school/madrasah aliyah (GSSS/VSSS/MA). The exogenous variables in this study is the percentage of realization government expenditure in education, gross domestic regional product per capita, ratio of pupils to teacher of JSS/MTs, and ratio of pupils to classes of JSS/MTs. The study found that percentage of realization government expenditure in education had no significant effect on the graduation rate of JSS/MTs and significant effect on the transition rate to GSSS/VSSS/MA. Gross domestic regional product per capita in this study have a significant effect on the graduation rate of JSS/MTs and the transition rate to GSSS/VSSS/MA. The ratio of pupils to teacher of JSS/MTs and the ratio of pupils per classes of JSS/MTs no significant effect either on the graduation rate of JSS/MTs and the transition rate to GSSS/VSSS/MA. As an intervening variable, a variable graduation rate of JSS/MTs was also no significant effect on the transition rate to GSSS/VSSS/MA.